Permeability behavior of silicon carbide‐based membrane and performance study for oily wastewater treatment. Issue 3 (12th January 2020) - Das, Dulal; Kayal, Nijhuma; Marsola, Gabriel Antonio; Damasceno, Leonardo Augusto; Innocentini, Murilo Daniel de Mello
Abstract: Porous SiC ceramic is considered as a suitable material for hot gas filtration, microfiltration, and many others industrial applications. However, full utilizations of porous SiC ceramics have been limited by high‐processing costs. In this study, mullite‐bonded porous SiC ceramics membranes were prepared using commercial SiC powder, alumina, clay, and different sacrificial pore formers. The effect of different pore formers on the microstructure, mechanical strength, porosity and pore size distribution, air, and water permeability of porous SiC ceramics were investigated. The average pore diameter, porosities, and flexural strength of the final ceramics varied in the range 3.7‐6.5 µm, 38‐50 vol. %, and 28‐38 MPa, respectively, depending on the characteristics of pore former. The Darcian (k1 ) and non‐Darcian (k2 ) permeability evaluated from air permeation behavior at room temperature was found to vary from 1.48 × 10 −13 to 4.64 × 10 −13 m 2 and 1.46 × 10 −8 to 6.51 × 10 −8 m, respectively. All membranes showed high oil rejection rate (89%‐93%) from feed wastewater with oil concentration of 1557 mg/L. The membrane with porosity 48 vol% and mechanical strength 31.5 MPa showed and highest pure water permeability of 13 298 Lm −2 h −1 bar −1 .